Phenolic Fractions from Walnut Milk Residue: Antioxidant Activity and Cytotoxic Potential - Pamela Ruth Toledo-Merma; María Fernanda Arias-Santé; Miguel Ángel Rincón-Cervera; Omar Porras; Raquel Bridi; Samantha Rhein; Martina Sánchez-Contreras; Paulina Hernandez-Pino; Nicolás Tobar; Luis Puente-Díaz; Adriano Costa de Camargo (Plants)
Walnut milk residues (WMR) were investigated for the first time through their phenolic characterization including soluble (free, esterified, and etherified) phenolics and those released from their insoluble-bound form (insoluble-bound phenolic hydrolysates, IBPHs) and their antioxidant properties. Free phenolics were recovered and alkaline or acid hydrolysis were used to recover the remaining phenolic fractions. Total phenolic compounds (TPCs) and their antioxidant activity were analyzed by Folin–Ciocalteu, FRAP, and ORAC methods, respectively. Soluble phenolics (free + esterified + etherified fractions) showed a higher TPC (275.3 mg GAE 100 g−1 dw) and antioxidant activity (FRAP: 138.13 µmol TE g−1 dw; ORAC: 45.41 µmol TE g−1 dw) with respect to the IBPH. There was a significant correlation between TPC and FRAP and ORAC values regardless of the fraction and tested sample. Phenolic acids and flavonoids were identified and quantified by ultra-performance liquid chromatography–electrospray tandem mass spectrometry (UPLC-ESI-MS/MS). Gallic acid, mainly in the free form (3061.0 µg 100 g−1), was the most representative, followed by biochanin A, identified for the first time in a walnut product and mostly present in the fraction released from the esterified form (593.75 µg 100 g−1). No detrimental cytotoxic impact on Caco-2 cells was observed. Hence, WMR could be considered a potential source for the development of nutraceutical and/or antioxidant food additives.